Psychological well-being and environmental identity: A cross-cultural study of young adults in Russia and France - Дарья Андреевна Теплова; Пётр Алексеевич Яркин (Психология человека в образовании)
Introduction. Contemporary society faces escalating environmental challenges, yet existing research lacks a comprehensive understanding of the interplay between psychological well-being, environmental identity, and value orientations across cultures. This study investigates these relationships among young adults in Russia and France using quantitative survey methods and statistical analysis.